2019
DOI: 10.1002/jcsm.12405
|View full text |Cite
|
Sign up to set email alerts
|

Early myopathy in Duchenne muscular dystrophy is associated with elevated mitochondrial H2O2 emission during impaired oxidative phosphorylation

Abstract: Background Muscle wasting and weakness in Duchenne muscular dystrophy (DMD) causes severe locomotor limitations and early death due in part to respiratory muscle failure. Given that current clinical practice focuses on treating secondary complications in this genetic disease, there is a clear need to identify additional contributions in the aetiology of this myopathy for knowledge‐guided therapy development. Here, we address the unresolved question of whether the complex impairments observed in DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(144 citation statements)
references
References 95 publications
(214 reference statements)
6
126
3
Order By: Relevance
“…This schematic has been partially adapted from Hughes et al . () using concepts from Meyer et al . (), Aliev et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This schematic has been partially adapted from Hughes et al . () using concepts from Meyer et al . (), Aliev et al .…”
Section: Resultsmentioning
confidence: 99%
“…The PCr is exported via VDAC into the cytosol while the ADP is directly recycled back via ANT into the mitochondrial matrix. This schematic has been partially adapted from Hughes et al (2019) using concepts from Meyer et al (1984), Aliev et al (2011 and Guzun et al (2012).…”
Section: Figure 2 Schematic Representation Of Energy Transfer Betweementioning
confidence: 99%
“…However, given that mitochondrial dysfunction has been linked to muscle atrophy during muscle inactivity, disturbances in mitochondrial biology may also be a feature contributing to the development and progression of muscle‐wasting conditions. In support of this proposition, there is growing evidence linking mitochondrial dysfunction to a number of muscular dystrophies, including Duchenne, spinal muscular atrophy, and the calpainopathy that induces limb girdle muscular dystrophy Type 2A (LGMD2A) . Whether it is also a trait of caveolinopathies such as LGMD1C has not yet been documented, but studies in cultured myoblasts and mice expressing the Cav3 P104L mutation have reported disordered glucose metabolism and altered expression of a number of mitochondrial proteins that regulate diverse aspects of mitochondrial structure and function .…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that the loss of dystrophin is accompanied by myofiber mitochondrial dysfunction and a concomitant increase in oxidative stress (Hughes et al, 2019;Kuznetsov et al, 1998;Pant et al, 2015;Schuh et al, 2012;Timpani et al, 2015b). Moreover, recent studies reported that restoration of mitochondrial bioenergetic function ameliorates pathological progression in the mouse model of DMD Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%